2017
DOI: 10.1038/srep45114
|View full text |Cite
|
Sign up to set email alerts
|

Biomimetic surface structuring using cylindrical vector femtosecond laser beams

Abstract: We report on a new, single-step and scalable method to fabricate highly ordered, multi-directional and complex surface structures that mimic the unique morphological features of certain species found in nature. Biomimetic surface structuring was realized by exploiting the unique and versatile angular profile and the electric field symmetry of cylindrical vector (CV) femtosecond (fs) laser beams. It is shown that, highly controllable, periodic structures exhibiting sizes at nano-, micro- and dual- micro/nano sc… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
122
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 162 publications
(130 citation statements)
references
References 36 publications
8
122
0
Order By: Relevance
“…only related with the pronounced enhanced ripple periodicity or depth due to the dissimilar spatial profile of the deposited energy but also with a different orientation of the produced profile. More specifically, the ripple formation induced by RP (see Fig.10 for NP=2) are concentric periodic structures that have also been observed experimentally in previous works 17,33,35,40,41 . Indeed, a simulated two-dimensional pattern that is illustrated in Fig.10a shows the surface profile while the height distribution is shown in Fig.10b.…”
Section: Resultssupporting
confidence: 81%
See 2 more Smart Citations
“…only related with the pronounced enhanced ripple periodicity or depth due to the dissimilar spatial profile of the deposited energy but also with a different orientation of the produced profile. More specifically, the ripple formation induced by RP (see Fig.10 for NP=2) are concentric periodic structures that have also been observed experimentally in previous works 17,33,35,40,41 . Indeed, a simulated two-dimensional pattern that is illustrated in Fig.10a shows the surface profile while the height distribution is shown in Fig.10b.…”
Section: Resultssupporting
confidence: 81%
“…It was shown that the spatial form of the RP does not only lead to structures of different periodicity compared to those induced if LP beams are used ( Fig.9) but also produce structures of (spatially) variable height ( Fig.7-8) and spatial distribution (Fig.10b). This is a significant prediction (which was verified experimentally for Ni in a previous work 33,35 or semiconductors 40,41 ) as it demonstrates the capability of controlling characteristics of morphological features with the use of different polarization states. It should be mentioned, though, that a systematic experimental validation of the numerical results is required to confirm the accuracy of the proposed model for irradiation of noble metals with small electron-phonon coupling constant.…”
Section: Resultssupporting
confidence: 71%
See 1 more Smart Citation
“…More specifically, laser beams with cylindrical states, namely radial and azimuthal polarization, have gained considerable attention in the past two decades, as the symmetry of the polarization enables new processing strategies [17] with applications in various fields including microscopy, lithography [18], electron acceleration [19], material processing [17,20,21] and optical trapping [22]. The so-called cylindrical vector beams (CVB) have been the topic of numerous theoretical and experimental investigations [20,[23][24][25][26][27][28][29]. A recent work on nickel irradiation with femtosecond pulses revealed morphological changes for LPB and CVB for various fluences and number of pulses [30].…”
Section: Introductionmentioning
confidence: 99%
“…Femtosecond lasers made it possible to structure the surface of various materials such as metals, 1 ceramics, 2,3 dielectrics 4,5 and semiconductors. 6 These modications are attributed to be linked to both laser induced structures and chemical surface composition changes during the irradiation. Laser induced structures, such as periodical formations like grooves and spikes, are reported to induce remarkable modications of surface wetting, 7-10 tribological, 11 and optical properties.…”
Section: Introductionmentioning
confidence: 99%